Field performance of grafted, micropropagated, and own-rooted plants of three Italian hazelnut cultivars during the initial four seasons of development - Traini, Chiara; Facchin, Simona Lucia; Brigante, Raffaella; Vinci, Alessandra; Persichetti, Sofia; Meneghini, Massimiliano; Micheli, Maurizio; Famiani, Franco; Portarena, Silvia; Dradi, Giuliano; Farinelli, Daniela (Frontiers in Plant Science, 2024)
Micropropagated, grafted on not suckering rootstock and own-rooted plants by layering from three Italian hazelnut (Corylus avellana L.) cultivars were established in the same orchard and environmental condition. Over the course of four consecutive years, a comparative study, for the first time, was carried out to assess their growth characteristics, vegetative and productive performances. We found that the micropropagated plants, regardless of the variety considered, even being smaller than the other plants at the beginning of the plantation, reached similar sizes as the other plants after four growing seasons. Furthermore, micropropagated plants exhibited greater uniformity in growth compared to grafted ones, while own-rooted plants displayed more variability. This suggests that the in vitro propagation technique, even in hazelnut, allows standardizing the plant material while preserving cultivar characteristics. No significant differences in yield performance and canopy volume were observed among the three propagation methods. This indicates that in vitro propagation as well as grafting can be safely recommended for the cultivation of hazelnut cultivars.